2019
DOI: 10.1016/j.stem.2019.02.015
|View full text |Cite
|
Sign up to set email alerts
|

A Human iPSC Double-Reporter System Enables Purification of Cardiac Lineage Subpopulations with Distinct Function and Drug Response Profiles

Abstract: Highlights d TBX5 Clover2 and NKX2-5 TagRFP reporter enables purification of 4 cardiac subpopulations d Different cardiac lineages differentiate into specific cardiac cell types d CORIN is a cell-surface marker for the TBX5+NKX2-5+ subpopulation d Lineage-specific cardiomyocyte subtypes can be used for precise drug testing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 39 publications
5
84
0
Order By: Relevance
“…Wildtype (WT) , GATA6 +/- , GATA6 -/- , and GATA6 R456G/R456G hiPSCs were processed for differentiation into cardiomyocytes (hiPSC-CMs) by modulation of the Wnt signaling pathway and subsequent metabolic selection via glucose deprivation ( Sharma et al, 2018b ). This protocol yields hiPSC-CMs that express first and second heart field genes ( Zhang et al, 2019 ). As previous single-cell RNA- sequencing (RNA-Seq) of cardiomyocytes isolated from developing mouse hearts ( DeLaughter et al, 2016 ) identified peak Gata6 expression in cardiac progenitors and early cardiomyocytes, we studied hiPSC-CMs at differentiation days 4 and 8, which approximate these in vivo developmental stages.…”
Section: Resultsmentioning
confidence: 99%
“…Wildtype (WT) , GATA6 +/- , GATA6 -/- , and GATA6 R456G/R456G hiPSCs were processed for differentiation into cardiomyocytes (hiPSC-CMs) by modulation of the Wnt signaling pathway and subsequent metabolic selection via glucose deprivation ( Sharma et al, 2018b ). This protocol yields hiPSC-CMs that express first and second heart field genes ( Zhang et al, 2019 ). As previous single-cell RNA- sequencing (RNA-Seq) of cardiomyocytes isolated from developing mouse hearts ( DeLaughter et al, 2016 ) identified peak Gata6 expression in cardiac progenitors and early cardiomyocytes, we studied hiPSC-CMs at differentiation days 4 and 8, which approximate these in vivo developmental stages.…”
Section: Resultsmentioning
confidence: 99%
“…Generation of SAN-like pacemaker cells from hPSCs has been achieved by mimicking the developmental steps known to be involved in SAN specification in vivo. As already described above, by using a standard CM differentiation protocol, Zhang and colleagues identified a subpopulation of NKX2.5 − /TBX5 + cells that further differentiated into functional SAN-like CMs, expressing SHOX2 , TBX3 and TBX18 [ 29 ], reinforcing the idea that SAN-like CMs arise from an NKX2.5 − population. Recently, Protze and colleagues [ 45 ] reported a directed differentiation protocol for generation of SAN-like CMs from hPSCs ( Figure 3 B).…”
Section: Cardiovascular Lineages Specification From Hpscs—lessons mentioning
confidence: 77%
“…Moving further along in the identification of the origin of the different subpopulations of CMs, a more recent work from Zhang and colleagues, using in vitro differentiation of hPSCs into cardiac progenitor cells [ 29 ], showed that NKX2.5 + /TBX5 + cells represent an FHF-like derived population, which predominantly differentiates into ventricular-like CMs that are genetically and functionally similar to left ventricular CMs, expressing HAND1 and KCNJ2 markers [ 29 ]. They also identified CORIN as a specific cell surface marker for the NKX2.5 + /TBX5 + subpopulation, enabling in this way the isolation of left ventricular CMs from a mixed population of hPSC-derived CMs.…”
Section: Cardiovascular Lineages Specification From Hpscs—lessons mentioning
confidence: 99%
“…This approach would be applicable to other human cell models, such as iPSC and ES-derived organoids. Although in these systems successful knock-in via conventional HDR approaches has already repeatedly been achieved [47][48][49] , use of an homology-independent-based strategy may increase the efficiency of knock-in generation.…”
Section: Discussionmentioning
confidence: 99%